MMP-9: Biomarker for abdominal aneurysm - Bin Affirul A.C.; Azim I.M.; Hanafiah H.; Nor Azmi K.; Rozman Z. (Societa Editrice Universo, 2024)
Prior studies have shown the correlation between MMP-9 concentration levels with AAA raising the probability of its usage as a biomarker in AAA disease. However, results of previous studies have been conflicting. The purpose of this study is to identify the correlation between MMP-9 concentration levels with AAA disease and further define the utility as a biomarker for our center population. Materials and Methods: This is prospective controlled trial. Peripheral venous blood sample is obtained from 20 patients with AAA and 36 normal control subjects. MMP-9 concentration levels were determined by an enzyme-linked immunosorbent assay and compared with subjects abdominal ultrasonography or computed tomography of abdomen. Results: Mean (SE) MMP-9 was 23.94 0.60 ng/mL in normal control subjects and 21.39 1.03 ng/mL in patients with AAAs (p ?0.05 versus normal control subjects). MMP-9 correlate significantly with AAA (p=0.004). There was no correlation of MMP-9 levels with age, gender, or other risk factors. The cutoff point is 12.54 for aorta size <3.0cm. The sensitivity and specificity of MMP-9 were 60% and 64% respectively. Conclusions: MMP-9 levels correlate significantly with AAA with a cutoff point of 12.54. However, the utility of MMP-9 as a diagnostic test is limited due to low sensitivity and specificity. An elevated MMP-9 has limited use to predict the presence of AAA (positive predictive value: 60%) and a normal MMP-9 level was insufficient to determine the absence of AAA (negative predictive value: 36.1%). Societ Editrice Universo (SEU).